Awareness, attitudes towards wastewater reuse and perceptions of public health risks among the general public in Cyprus - Lamnisos, Demetris; Anastasiou, C.; Grafias, P.; Panayi, A.; Larkou, A.; Georgiou, E.; Middleton, Nicos (My University, 2013)
Background.As wastewater reuse is becoming imperative in water scarce regions, in addition to evaluation of the extent of potential health risks involved, an assessment of public acceptance is necessary for a sustainable water reuse scheme to be successful.Objectives: To investigate public awareness, attitudes and health risk perceptions of water reuse among the general public in Cyprus.
Keywords: Public health; Health risks; Wastewater reuse